Resource Misallocation and Rice Productivity in Thailand - Siwapong Dheera - Aumpon (Montenegrin Journal of Economics, 2018)
Thailand’s manufacturing sector is characterised by considerable resource misallocation compared with this sector in other countries, and the problem may extend to its agricultural sector as well. Using detailed household-level data on rice production from the 2013 Agricultural Census, this paper examines resource misallocation across farms in Thailand and its effect on the country’s aggregate productivity in rice farming. I find that the marginal products of land and capital were largely dispersed, which is an indication of significant resource misallocation. I further estimate that reallocation of resources could increase aggregate output and productivity by approximately a factor of 1.67. This potential gain is not small, but it is smaller than that predicted in other studies for the Thai manufacturing sector and the Malawian agricultural sector, a result suggesting that the Thai rice farming sector is relatively less plagued by resource misallocation. Other developing countries may encounter similar degrees of misallocation in their agricultural sectors. I also find that an effective reallocation policy cannot involve simply reducing the landholdings of large landholders but rather supports highproductivity farmers to have more land and capital.